Brain-clinical biotyping in patients with idiopathic REM sleep behavior disorder - Shi Tang; Bei Huang; Yanlin Wang; Yaping Liu; Jing Wang; Li Zhou; Siyi Gong; Yuhua Yang; Joey WY Chan; Steven WH Chau; Winnie CW Chu; Jill Abrigo; et al. (npj Parkinson's Disease)
Abstract Idiopathic REM sleep behavior disorder (iRBD) is a prodromal stage of α-synucleinopathies including Parkinson’s disease (PD), yet its clinical heterogeneity remains underexplored. This study aimed to identify novel brain-clinical biotypes in iRBD by integrating structural MRI and clinical assessments. We included 172 patients with video-polysomnography-confirmed iRBD and 126 controls who underwent multimodal MRI and clinical evaluation. Similarity Network Fusion was used to integrate cortical thickness, surface area, subcortical volume, and clinical data, followed by spectral clustering to identify iRBD biotypes. Two distinct biotypes were identified: Biotype 1 showed widespread cortical-subcortical-cerebellar atrophy, functional hypoconnectivity, more motor and cognitive deficits with higher prodromal PD risk; Biotype 2 demonstrated increased surface area in limbic and parietal regions, cortical-cerebellar hyperconnectivity, and preserved neurocognitive function. These findings underscore the presence of distinct neurobiological subtypes in iRBD, highlighting the need for longitudinal monitoring to clarify their trajectories and implications for disease progression.